(untitled) (ARS, 2019)
This article proposes a reflection on the analysis of artworks endowed with artificial intelligence, raising questions such as autonomy and creativity. First, some contemporary artworks are offered as examples while the problem of creative autonomy in which these artworks are commonly interpreted is discussed. References to evolutive algorithms and Cybernetics culminate in a particular model for artwork analysis in terms of syntax, semantics and pragmatics. Such model offers a possible segmentation of the spectra of human creativity, while clarifying some of the current challenges for the development of creative machines. Finally, an artistic proposal is shown, which uses artificial intelligence to make drawings, in a situation in which the machine influences, interferes and redefines a creative process that dilutes the artist’s intentionality.